The The Appointment of Active Indonesian National Armed Force as Acting Regional Heads Based on Good Governance Principles - Pratama, Muhammad Rezky; Harianto, Aries; Firdaus, Fahmi Ramadhan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The 2024 Regional Election are the first time simultaneous national Regional Election have been held. As a result, 271 regional head positions are vacant due to the expiration of their term of office. Acting Regional Heads were appointed to fill in temporarily. One of the polemics is that an active Indonesian National Armed Force’s member was appointed as Acting Regent of West Seram. This research is a normative juridical research with statutory, conceptual, and historical approaches. The results showed that the Good Governance Principles has been regulated in Law Number 28 of 1999 concerning Clean and Free State Administration from Corruption, Collusion and Nepotism and Law Number 30 of 2014 concerning Government Administration, which when juxtaposed, there is 1 principle in common, namely the principle of legal certainty. The appointment of active Indonesian National Armed Force as Acting Regional Heads is not by the principle of legal certainty. The appointment contrary to Article 47 paragraph (1) of the Law Number 34 of 2004 concerning the Indonesian National Armed Force as the “lex specialis”. The appointment is also not by the Good Governance Principles construction in Article 10 of the Law 30/2014 because it violates the principle of legal certainty, accuracy, not abusing authority, openness, and good service. It is recommended that the Government in making the appointment of Acting Regional Heads should be guided by the Good Governance Principles and provide opportunities for the people to be involved so becomes more transparent and by democratic values.